Some Issues of Reintegration of the Migrants Returning to Armenia - Chobanyan, Haykanush (Journal of Sociology: Bulletin of Yerevan University, 2013)
The issues of the migrants returning to Armenia and their reintegration in the country of their origin are discussed in the present article. Someinstitutional, economic and social aspects of the reintegration of returning migrants, as well as other related factors (migration projects, human, financial and cultural capital) are also discussed in the article. Different models of reintegration, institutionale basis, as well as the Armenian experience of solving the problems of returning migrants have also been analysed.